Constructing the optimal experimental autoimmune thyroiditis mouse model using porcine thyroglobulin - Liu, Ke; Zhang, Pei; Jin, Zi-Shan; Meng, Xiang-Kun; Luo, Jin-Li; Han, Lin; Yu, Xiao-Tong (Frontiers in Immunology, 2025)
IntroductionAutoimmune thyroiditis (AIT) is a chronic autoimmune disease characterized by lymphocytic infiltration of the thyroid gland and elevated specific antibodies. Its incidence rises annually, yet no standardized animal model fully mimics human AIT. Given unclear pathogenesis and lack of targeted immunotherapies, researchers invest significant time in developing suitable models. This study systematically compares pathological and immunological effects of different immunization conditions (antigen dose, frequency, administration methods) in NOD/LtJ mice to establish an optimal model for elucidating AIT pathogenesis and therapies.MethodsEighty female NOD/LtJ mice were divided into subcutaneous (SC) and tail vein intravenous (IV) injection groups. SC groups received porcine thyroglobulin (pTg) emulsified in CFA (primary) and IFA (booster), with doses of 50/100/200 μg and frequencies of 2 or 3 immunizations. IV groups received pTg in PBS followed by LPS (3 immunizations: weeks 1, 3, 4). All model groups drank 0.05% NaI water. Thyroid histopathology (HE staining, infiltration scoring), serum TPO-Ab/TG-Ab (ELISA), cytokines (multiplex assay), Th17/Treg cells (multiplex immunofluorescence), and thyroid IL-17A/NLRP3/Caspase-1 (immunohistochemistry) were analyzed 2 weeks post-last immunization.ResultsHigh-dose antigen (200 μg pTg) with high-frequency immunization (three times) via SC or IV routes induced severe thyroid lymphocyte infiltration (scores: SC 3.4±0.55, IV 3.2±0.45; p<0.01 vs. controls), follicular destruction, and elevated serum antibodies (TPO-Ab: IV 438.8±13.15 > SC 406.2±7.46; TG-Ab: IV 158.4±5.32 > SC 141.9±2.36). This protocol activated Th1/Th17 cytokines (IL-17A, IL-6, TNF-α), increased Treg cells (p<0.001), and specifically enhanced NLRP3 (p<0.001) and Caspase-1 in thyroid tissue, with IV injection showing superior antibody production and inflammasome activation.DiscussionThe combination of high-dose pTg (200 μg) and three immunizations maximally induced AIT pathology and immune responses in NOD/LtJ mice. Tail vein injection excelled in stimulating antibody production and NLRP3 activation, while subcutaneous injection promoted stronger histological inflammation. After balancing operational feasibility, pathological reproducibility, and immunological specificity, three subcutaneous and intravenous tail injection of 200 μg pTg are recommended as the optimal modeling protocol. This approach accelerates model selection, improves experimental efficiency, and reduces animal use, providing a robust foundation for AIT research.